Ambitious databases on the Americas and Caribbean - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
AgroInfo Americas is a set of free agricultural and livestock databases accessible by the Internet